MENJELAJAHI DUNIA REDOKS DENGAN REACT: PENDEKATAN PEMBELAJARAN INOVATIF TERHADAP HASIL BELAJAR SISWA SMA - Pohan, Heni Mulyani; Harahap, Fatma Suryani; Siregar, Rabiatul Adawiyah; Lubis, Fitri Agustina; Sahara, Nur; Junita, Hafni; Ritonga, Siti Nurzainab (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2024)
The birth of the REACT Model was initiated by CORD in the United States. This learning approach includes five learning principles which include the relationship between concepts (Relating), direct experience (Experiencing), application in real situations (Appliying), cooperation between students (Cooperating) and transfer of learning to other situations (Transferring). This learning approach makes it easier for students to understand and master redox reaction material. The aim of the research is that it is hoped that through this research, it will be possible to find out to what extent the REACT learning model contributes to improving student learning outcomes in understanding the concept of redox reactions. This study is a quantitative study. The sampling method for this study is random sampling. Collect data through learning outcomes tests. In the experimental class the average score obtained after implementing the REACT learning model was 73.33 and 60.33 in the control class and the results of the independent t test using SPSS obtained a sig value of 0.025 < 0.05 which shows that the REACT learning model can improve results. Study.